2021
DOI: 10.1183/23120541.00432-2021
|View full text |Cite
|
Sign up to set email alerts
|

Blood eosinophils as a predictor of treatment response in adults with difficult-to-treat chronic cough

Abstract: There is lack of evidence on the role of blood eosinophil count (BEC) as a predictor of treatment response in patients with chronic cough (CC). The study aimed to evaluate BEC as a predictor of treatment response in all non-smoking adults with CC and normal chest X-ray referred to cough clinic and in subgroup of patients with CC due to asthma or NAEB (non-asthmatic eosinophilic bronchitis).This prospective cohort study included 142 consecutive, non-smoking patients referred to our cough centre due to CC. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
1
2
0
1
Order By: Relevance
“… 7 , 16 , 17 , 26 , 27 , 28 A recent study enrolling 142 adult chronic coughers found that there was a weak correlation between the blood eosinophil counts and sputum eosinophil (r = 0.30). 29 In the present study, we found that the level of blood eosinophil counts was moderately correlated with the percentage of sputum eosinophils (r = 0.54) in chronic coughers. Additionally, our results revealed that blood eosinophil counts ≥0.155 × 10 9 /L indicated a more likelihood of airway eosinophilia-related chronic cough, with an optimal sensitivity (78.9%) and specificity (70.3%).…”
Section: Discussionsupporting
confidence: 57%
“… 7 , 16 , 17 , 26 , 27 , 28 A recent study enrolling 142 adult chronic coughers found that there was a weak correlation between the blood eosinophil counts and sputum eosinophil (r = 0.30). 29 In the present study, we found that the level of blood eosinophil counts was moderately correlated with the percentage of sputum eosinophils (r = 0.54) in chronic coughers. Additionally, our results revealed that blood eosinophil counts ≥0.155 × 10 9 /L indicated a more likelihood of airway eosinophilia-related chronic cough, with an optimal sensitivity (78.9%) and specificity (70.3%).…”
Section: Discussionsupporting
confidence: 57%
“…However, increased blood eosinophils were not always found in patients with eosinophilic bronchitis, confirmed by sputum eosinophilia ( 32 ). A recent observational study showed the weak power of blood eosinophils as a predictor of treatment response in chronic cough ( 33 ). Furthermore, there is no RCT evidence.…”
Section: Discussionmentioning
confidence: 99%
“…All patients underwent diagnostic procedures, including pulmonary function testing, sputum induction, methacholine and capsaicin challenge prior to treatment administration. 12 This step-wise diagnostic algorithm was based on European Respiratory Society and American College of Chest Physicians guidelines. 11 , 13 Methacholine challenge was performed according to the American Thoracic Society guidelines, in a 2-minute tidal breathing protocol.…”
Section: Methodsmentioning
confidence: 99%